Stability and change in autism spectrum disorder diagnosis from age 3 to middle childhood in a high-risk sibling cohort. (October 2016) - Brian, Jessica; Bryson, Susan E; Smith, Isabel M; Roberts, Wendy; Roncadin, Caroline; Szatmari, Peter; Zwaigenbaum, Lonnie
Considerable evidence on autism spectrum disorder emergence comes from longitudinal high-risk samples (i.e. younger siblings of children with autism spectrum disorder). Diagnostic stability to age 3 is very good when diagnosed as early as 18–24 months, but sensitivity is weaker, and relatively little is known beyond toddlerhood. We examined stability and change in blinded, clinical best-estimate diagnosis from age 3 to middle childhood (mean age = 9.5 years) in 67 high-risk siblings enrolled in infancy. Good agreement emerged for clinical best-estimate diagnoses (89.6% overall; kappa = 0.76, p < 0.001, 95% confidence interval = 0.59–0.93). At age 3, 18 cases (26.9%) were classified with "autism spectrum disorder": 17 retained their autism spectrum disorder diagnosis (94.4%; 13 boys, 4 girls) and 1 no longer met autism spectrum disorder criteria at follow-up. Among "non–autism spectrum disorder" cases at age 3, 43/49 remained non–autism spectrum disorder at follow-up (87.8%; 22 boys, 21 girls) and 6/49 met lower autism symptomatology criteria ("Later-Diagnosed"; 3 boys, 3 girls). Later-diagnosed cases had significantly lower autism spectrum disorder symptomatology and higher receptive language at age 3 and trends toward lower autism symptoms and higher cognitive abilities at follow-up. Emerging developmental concerns were noted in all later-diagnosed cases, by age 3 or 5. High-risk children need to be followed up into middle childhood, particularly when showing differences in autism-related domains.